2020
DOI: 10.3389/fpsyt.2020.00385
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Status and Psychological Risk for Suicide Attempt: A Serial Multiple Mediation Model of Social Support and Emotion Regulation

Abstract: The current study examined the relation between sexual minority status, social support, emotion dysregulation, and suicide attempt in a community sample. A total of 388 community and college adults completed a one-time survey examining self-injury and suicidality. Findings demonstrated that that social support and emotion regulation, independently and in sequence, mediated the relation between sexual minority status and suicide attempt. The reverse mediation model with emotion regulation as the first mediator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Existing literature has not addressed regarding the unidimensionality (the prerequisite for parcelling) of SK and SJ, thus the original items of SK and SJ were retained in the SEM model. Despite little theoretical or empirical evidence supporting the possibility of a reverse mediation, we tested the reverse model (ACEs → PTSD/DSO → SK/ SJ) statistically (Chang, Fehling, & Selby, 2020) because of a cross-sectional study. Of note, given that ACEs were retrospective events before 18 years old and current PTSD/DSO and self-kindness/self-judgement status might not have an influence on, models with ACEs as a dependent variable were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has not addressed regarding the unidimensionality (the prerequisite for parcelling) of SK and SJ, thus the original items of SK and SJ were retained in the SEM model. Despite little theoretical or empirical evidence supporting the possibility of a reverse mediation, we tested the reverse model (ACEs → PTSD/DSO → SK/ SJ) statistically (Chang, Fehling, & Selby, 2020) because of a cross-sectional study. Of note, given that ACEs were retrospective events before 18 years old and current PTSD/DSO and self-kindness/self-judgement status might not have an influence on, models with ACEs as a dependent variable were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provided a novel insight regarding COVID-19 stress management at HIV clinics, particularly on the importance of institutional support. Previous studies showed that healthcare providers in supportive working environments were inclined to exhibit greater resilience-related abilities, including emotional regulation [47], self-efficacy [48], and adaptive coping strategies [49]. In facing a public health emergency, sufficient institutional support might enable HIV healthcare providers to use their internal coping recourses (i.e., resilience) and facilitate providers' adaptive coping instead of being overwhelmed to deal with COVID-19 stressors, resulting in reduced levels of distress.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the extent to which rejecting and accepting interpersonal experiences are associated with depression among LGBTQ youth, relatively few studies have examined the mechanisms underlying these associations. Consistent with the psychological mediation framework, 18 studies have demonstrated that experiences of discrimination and victimization may "get under the skin" (i.e., affect mental health) by contributing to general psychological processes (e.g., emotion dysregulation, rumination) 19 21 and sexual minority-specific processes (e.g., internalized stigma, rejection sensitivity). 22 Meanwhile, social support may contribute to lower depression by increasing self-esteem 23 and decreasing hopelessness.…”
Section: Introductionmentioning
confidence: 96%